Seed release by a serotinous pine in the absence of fire: implications for invasion into temperate regions - Wyse, Sarah V (AoB Plants, 2019)
In pines, the release of seeds from serotinous cones is primarily considered a response to the high temperatures of a fire. However, the naturalization of serotinous pines in regions where fires are rare highlights the need to quantify environmental conditions that determine seed release to allow accurate prediction of dispersal and spread risk. We investigated the conditions that break cone serotiny in Pinus radiata, a widely planted forestry species that has naturalized in temperate regions worldwide. We quantified the cone temperatures at which cones open in this species, while also assessing potential confounding effects of cone moisture and age on these temperature requirements. We compared our laboratory results with cone opening behaviour under typical field conditions during summer in Canterbury, New Zealand. Cones opened at a mean temperature of 45 °C, much higher than maximum ambient air temperatures recorded in New Zealand. We found no influence of cone age or moisture content on opening temperature. Under field conditions, cones opened upon reaching similar temperatures to those determined in the laboratory; however, passive solar heating caused cones to reach temperatures up to 15 °C higher than ambient conditions. This resulted in 50 % of cones opening in field conditions where maximum air temperatures never exceeded 30 °C. Our results highlight the need for complementary laboratory and field experiments for understanding seed release from serotinous cones. Our findings have important implications for weed risk assessments, showing that serotinous pines can release seed in temperate climates without fire.